Endemic tenebrionids (Coleoptera: Tenebrionidae) from the Patagonian steppe: a preliminary identification of areas of micro-endemism and richness hotspots - Carrara, Rodolfo (2012)
Based on data from sixteen museum collections we listed the endemic tenebrionids that inhabit the Patagonian steppe. Then, according to the geographical location of the species, we identified areas of micro-endemism and hotspots within this biogeographic province. Results showed 115 endemic tenebrionid species from the Patagonian steppe, 25 areas of micro-endemism and five hotspots. We used these outcomes to identify areas of importance for conservation. Based on the comparison with other biogeographic provinces, we suggest that the Patagonian steppe constitutes a center of high endemism for tenebrionids. We hypothesize that the isolation of the Patagonian steppe from other arid areas would cause the high occurrence of endemism. In addition, we suggest processes that could be responsible for the origin of the areas of micro-endemism and hotspots identified in this work.